Clinical Examination, Spondylolysis and Adolescent Athletes - Sundell, C.-G.; Jonsson, H.; Ådin, L.; Larsén, K. H. (International Journal of Sports Medicine, 2013)
Symptomatic spondylolysis is a stress reaction caused by microtrauma during physical exercise, an imaging diagnostic subgroup of Adolescent Low Back Pain (ALBP), found in adolescent athletes. Early diagnosis increases the possibility of healing. Thus, it is important to divide ALBP into subgroups. The aim of this study was to evaluate clinical tests that can distinguish symptomatic spondylolysis from other forms of ALBP in order to facilitate early referral for diagnostic imaging. The investigation subjects were a prospective case series with a control group, 25 subjects with ALBP and 13 subjects that had no history of LBP. The 2 groups were examined using the same clinical protocol. MRI of the whole lumbar spine was performed in both the case and control groups and CT investigations of the L4 and L5 vertebrae were performed in the case group. Significant differences between the 2 groups were found in 8 of our clinical tests. No clinical test, alone or in combination, could distinguish between spondylolysis and other forms of ALBP. As 88% of the subjects in the case group had MRI findings and almost 50% had spondylolysis, MRI should be performed at an early age in young athletes with ALBP.
Keywords: low back pain; stress fracture; stress reaction